Vitamin D, FOXO3a, and Sirtuin1 in Hashimoto's Thyroiditis and Differentiated Thyroid Cancer - Roehlen, Natascha; Doering, Claudia; Hansmann, Martin-Leo; Gruenwald, Frank; Vorlaender, Christian; Bechstein, Wolf Otto; Holzer, Katharina; Badenhoop, Klaus; Penna-Martinez, Marissa (Frontiers in Endocrinology, 2018)
Background: Protective effects of vitamin D have been reported in autoimmune and malignant thyroid diseases, though little is known about the underlying mechanism. Sirtuin 1 histon deacethylase (SIRT1) links the vitamin D pathway with regulation of transcription factor FOXO3a, a key player in cell cycle regulation and apoptosis. Aim of the present study was to investigate common single nucleotide polymorphisms (SNP’s) in FOXO3a gene in respect to thyroid diseases, as well as to evaluate the hypothesis of Sirtuin1-FOXO3a interaction being a mediator of anti-proliferative vitamin D effects. Methods: The SNP’s FOXO3a rs4946936/rs4945816/rs9400239 were genotyped in 257 patients with differentiated thyroid carcinoma (DTC), 139 patients with Hashimoto thyroiditis (HT) and 463 healthy controls (HC). Moreover, T-helper cells of HC and papillary thyroid cancer cell line BCPAP were incubated with 1,25(OH)2D3 and/or SIRT1 inhibitor Ex-527 in order to elucidate SIRT1- dependent vitamin D effects on cell proliferation and FOXO3a gene expression in vitro. Results: Patients with DTC tended to carry more often allele C in FOXO3a rs4946936 in comparison to HC (pcorrected=pc=0.08). FOXO3a rs9400239T and rs4945816C was more frequent in HT in comparison to HC (pc=0.02 and pc=0.01, respectively). In both DTC and HT, we could not find a correlation of FOXO3a SNP’s with vitamin D status. However, on in vitro level, 1,25(OH)2D3 showed an anti-proliferative effect in both T-helper cells and BCPAP, that was blocked by SIRT1 inhibition (T-helper cells: p=5.9 x 10-3, BCPAP: p=0.04) and accompanied by elevated FOXO3a gene expression in T-helper cells (p=0.05). Conclusions: FOXO3a rs9400239T and rs4945816C may constitute risk factors for HT, independent of the vitamin D status. This indicates the implication of FOXO3a in pathogenesis of autoimmune thyroid diseases. The dependency of anti-proliferative vitamin D effects on SIRT1 activity further suggests a key role of vitamin D-SIRT1-FOXO3a axis for protective vitamin D effects.